Enrichment of Nur77 mediated by RARβ leads to apoptosis of human hepatocellular carcinoma cells induced by fenretinide and HDACi - Yang, Hui (2011)
Synthetic retinoid fenretinide is one of the most promising clinically tested retinoids. Previously, we have shown that fenretinide induces apoptosis of Huh7 cells, but HepG2 cells are relatively resistant to fenretinide-induced apoptosis. The current study examines the interactive role of fenretinide and histone deacetylase inhibitors (HDACi) in inducing apoptosis of human hepatocellular carcinoma (HCC) cells and the underlying mechanism. Trichostatin A (TSA) and scriptaid can either enhance fenretinide-induced apoptosis in the fenretinide sensitive HCC cells (Huh7 and Hep3B) or sensitize the fenretinide resistant cells (HepG2) to become sensitive to the apoptotic effect of fenretinide in a cancer-cell specific manner. The sensitivity of cells to fenretinide-induced apoptosis was neither associated with ROS production nor anti-oxidant gene expression. However, the level of RARβ and Nur77 was important for inducing apoptosis. Upon fenretinide and HDACi treatment, the expression of RARβ and Nur77 were induced and co-localized in the cytosol. The induction of Nur77 protein level, but not the mRNA level, was RARβ-dependent. In addition, RARβ interacted with Nur77. Nur77 was essential for fenretinide- and HDACi-induced apoptosis of Huh7 cells. Induction of the expression, the interaction, and the nuclear export of RARβ and Nur77 mediate fenretinide and HDACi induced apoptosis. Our findings suggest that targeting Nur77 and RARβ simultaneously provides an effective way to induce HCC cell death.